Do building energy codes adequately reward buildings that adapt to partial occupancy?. (3rd July 2019) - O'Brien, William; Gunay, H. Burak
Abstract : Most building energy codes' performance path implicitly reward buildings that perform well under steady and near-capacity occupancy conditions, even though these are not typical operating conditions. Partially, as a result, our buildings tend not to be designed with features that allow optimal energy performance in the common circumstance of partial and fluctuating occupancy. The objective of this paper is to examine current building energy codes in this regard. The paper uses a simulation-based approach to demonstrate two strategies that target occupancy-adaptability: demand-controlled ventilation and smaller-than-required lighting control zones with occupancy-controlled lighting. In this paper, a code-compliant EnergyPlus archetype office building in Toronto, Canada was used to evaluate these design features under different occupancy conditions. The results confirm that both demand-controlled ventilation and smaller lighting control zones are most advantageous at lower occupancy levels. Accordingly, the paper concludes with generalized recommendations for code modifications to properly credit buildings with greater adaptability to partial occupancy.